2018
DOI: 10.1038/s41598-018-20608-6
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Innate Lymphocytes Actuate Immunity Against Tumours and Limit Cancer Metastasis

Abstract: Type 2 innate lymphoid cells (ILC2) potentiate immune responses, however, their role in mediating adaptive immunity in cancer has not been assessed. Here, we report that mice genetically lacking ILC2s have significantly increased tumour growth rates and conspicuously higher frequency of circulating tumour cells (CTCs) and resulting metastasis to distal organs. Our data support the model that IL-33 dependent tumour-infiltrating ILC2s are mobilized from the lungs and other tissues through chemoattraction to ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 53 publications
2
99
0
Order By: Relevance
“…IL-33-induced ILC2s can amplify inflammatory immune responses during immune-mediated hepatitis (58). It is also reported that ILC2s play a fundamental role in enhancing anticancer immunity and controlling tumor metastasis (62). We observed significant increase of ILC2s in liver of the IL-33 group during HCC development ( Supplemental Fig.…”
Section: Discussionsupporting
confidence: 54%
“…IL-33-induced ILC2s can amplify inflammatory immune responses during immune-mediated hepatitis (58). It is also reported that ILC2s play a fundamental role in enhancing anticancer immunity and controlling tumor metastasis (62). We observed significant increase of ILC2s in liver of the IL-33 group during HCC development ( Supplemental Fig.…”
Section: Discussionsupporting
confidence: 54%
“…In subsequent studies, Gao et al [ 77 ] showed that over-expression of IL-33 in B16 melanoma and 4T1 breast cancer cells inhibited tumor growth and metastasis by increasing the numbers and IFN-γ production of CD8 + T and NK cells in tumor tissues, creating a TME that favored the eradication of tumors [ 77 ]. More recent studies showed that IL-33 can regulate cytokines to mobilize Type 2 innate lymphoid cells (ILC2) from the lung and other tissues into tumor beds where they orchestrate tumor immune-surveillance in cooperation with dendritic cells to promote cytolytic T cell responses, thereby enhancing anti-cancer immunity and controlling metastasis [ 98 ].…”
Section: The Role Of Il33/st2 In Tumorigenesismentioning
confidence: 99%
“…Indeed, their tissue-repair function can induce cholangiocarcinoma and liver metastasis ( 121 ). ILC2s can also be mobilized from the lung and other tissues thanks to IL-33, to penetrate tumors, mediate immune-surveillance with DC, and promote adaptive cytolytic T cell responses and attraction ( 122 , 123 ).…”
Section: Direct or Indirect Effects Of Il-33 As A Tumor Suppressormentioning
confidence: 99%